2019
DOI: 10.1038/s41598-019-47839-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in fetal growth velocity

Abstract: Fetal growth quality is associated with susceptibility to non-communicable diseases. Fetal size has been conventionally assessed using the averaged growth chart, but fetal growth velocity has recently been attracting attention as another important aspect of fetal development. Since fetal growth velocity may reflect fetal response to various conditions during the developmental process within the maternal constraint, it is reasonable to imagine that there might exist a physiological diversity in growth velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…FGR is classified into two categories according to the gestational age of onset and nearly 80% are late-onset (≥ 32 weeks) 15 . The trajectory of individual fetal growth velocity is a valid indicator for fetal growth assessment 16 . We previously showed that heterogeneity of growth velocity trajectories is most pronounced after 30 weeks of gestation 16 .…”
Section: Mainmentioning
confidence: 99%
See 3 more Smart Citations
“…FGR is classified into two categories according to the gestational age of onset and nearly 80% are late-onset (≥ 32 weeks) 15 . The trajectory of individual fetal growth velocity is a valid indicator for fetal growth assessment 16 . We previously showed that heterogeneity of growth velocity trajectories is most pronounced after 30 weeks of gestation 16 .…”
Section: Mainmentioning
confidence: 99%
“…The trajectory of individual fetal growth velocity is a valid indicator for fetal growth assessment 16 . We previously showed that heterogeneity of growth velocity trajectories is most pronounced after 30 weeks of gestation 16 . In our cohort, ≥10% of the fetuses showed a third-trimester growth acceleration or deceleration.…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations
“…To image osteoclasts involved in osteoporosis, spongy bone tissue was immuno-labelled for the osteoclast marker cathepsin K and imaged by ASEM [4]. Cathepsin K protease secreted by osteoclasts digests bone collagen and thus plays a critical role in bone absorption.…”
mentioning
confidence: 99%